An Overview of US Papaya Production, Trade, and Consumption - Edward A. Evans; Fredy H. Ballen; Jonathan H. Crane (EDIS)
The United States produces close to 14,000 t of papaya annually. Consumption of the fruit is on the upswing, and the development of new cultivars tolerant to the Papaya Ring Spot Virus encourage many growers in South Florida to take a second look at producing papaya for the domestic market. This 8-page fact sheet provides information on domestic trends in the production and trade of fresh papaya in the U.S. Also included is a price analysis at the wholesale level for representative markets on the US East and West Coasts. Written by Edward A. Evans, Fredy H. Ballen, and Jonathan H. Crane, and published by the UF Department of Food and Resource Economics, September 2012.